Langerhans Cells—Programmed by the Epidermis - Clayton, Kalum; Vallejo, Andres F.; Davies, James; Sirvent, Sofia; Polak, Marta E. (Frontiers in Immunology, 2017)
Langerhans cells (LCs) reside in the epidermis as a dense network of immune system sentinels. These cells determine the appropriate adaptive immune response (inflammation or tolerance) by interpreting the microenvironmental context in which they encounter foreign substances. In a normal physiological, "non-dangerous" situation, LCs coordinate a continuous state of immune tolerance, preventing unnecessary and harmful immune activation. Conversely, when they sense a danger signal, for example during infection or when the physical integrity of skin has been compromised as a result of a trauma, they instruct T lymphocytes of the adaptive immune system to mount efficient effector responses. Recent advances investigating the molecular mechanisms underpinning the cross-talk between LCs and the epidermal microenvironment reveal its importance for programming LC biology. This review summarises the novel findings describing LC origin and function through the analysis of the transcriptomic programmes and gene regulatory networks (GRNs). Review and meta-analysis of publicly available datasets clearly delineates LCs as distinct from both conventional DCs and macrophages, suggesting a primary role for the epidermal microenvironment in programming LC biology. This concept is further supported by the analysis of the effect of epidermal pro-inflammatory signals, regulating key GRNs in human and murine LCs. Applying whole transcriptome analyses and in silico analysis has advanced our understanding of how LCs receive, integrate and process signals from the steady state and diseased epidermis. Interestingly, in homeostasis and under immunological stress, the molecular network in LCs’ remains relatively stable, reflecting a key evolutionary need related to tissue localisation. Importantly, to fulfil their key role in orchestrating anti-viral adaptive immune responses, LC share specific transcriptomic modules with other DC types able to cross-present antigens to cytotoxic CD8+ T cells, pointing to a possible evolutionary convergence mechanism. With the development of more advanced technologies allowing delineation of the molecular networks at the level of chromatin organisation, histone modifications, protein translation and phosphorylation, future “omics” investigations will bring in-depth understanding of the complex molecular mechanisms underpinning human LC biology.